Reinforcing effects of graphene oxide in oil well cement used for CO₂ storage: article - Rusbi, Muhammad Iqbal; Sauki, Arina (2018)
CCS or Carbon Capture and Storage is one of the method to conserve environment by reducing the CO₂ gas emission to the atmosphere by the process of separation and capture of carbon dioxide and safely store the CO₂ into deep geologic formations. Wellbore and cement integrity need to be maximized for safely and permanently storing of carbon dioxide (CO₂) in the subsurface for a very long term of duration. The chemical interactions between CO₂ in carbonic acid and cements will form calcium carbonate that easily leachable or susceptible to further reaction that could potentially diminish the strength of the cement and increase the cement degradation rate that can lead to leakage. The reinforcing effects of graphene oxide (GO) in oil well cement used for CO₂ storage was investigated in this experimental study. GO was prepared by oxidization and ultrasonic dispersion. Effects of GO on mechanical properties of cement cubes after been exposed to carbonic acid for 10 days were investigated by determining the compressive strength and mass losses of the cement cubes and the results were compared with neat cement without GO. It is discovered that when 0.10 wt.% by weight of GO was added into the cement paste, compressive strength was increased by more than 24% and it due to the refinement of the porosity of the cement matrix caused by strong covalent bond that form flower-like crystal regulated by GO and can reduce the degradation rate of the cement by more than 32% because GO have various oxygencontaining functional groups that make GO highly attractive for cement hydration that needed in order to get strong and lower degradable compound of cement. The overall results show that GO is an effective nanomaterial for reinforcing the mechanical properties of oil well cement used for CO₂ storage.